ALTERNATIF BAGI PENGUATAN DEMOKRASI: PENGALAMAN MEKANISME ANGGARAN PARTISIPATIF (PARTICIPATORY BUDGETING) DI KOTA PORTO ALEGRE, BRAZIL - Zikril Hakim Badri (Review of International Relations, 2020)
As a form of government in which the people who are sovereign and in power to determine their lives, democracy not only provides a breath of fresh openness and freedom but also promises a million hopes for a prosperous people's life. However, in line with the history of mankind, the government system that is predicted to be the best model of government from the worst, are also not free from problems, criticisms and crises that occur in it. The sovereignty of the people which has become the spirit of democracy has been eroded by the problem of the crisis of representation and direct involvement of the people in policy making. Democracy as a model of government reaps a crisis of public confidence which starts to regard this government system as an illusion of prosperity and justice. Interestingly, in the midst of the storm of problems that have plagued the democratic governance system in the present era, a breath of a new fresh air has emerged for the continuity of the sovereignty-based government system. In the city of Porto Alegre, Brazil, which is one of the main countries in the Latin American region, alternatives for strengthening participatory democracy have emerged through a model of governance based on Participatory Budgeting. "The implementation of this Participatory Budgeting has turned out to be able to restore the vital role of the people in policy making while at the same time improving the model of modern democratic governance which is increasingly hit by a crisis of trust and legitimacy from the people of today." Keywords: Democracy, crisis of representation, alternative democracy, participatory budgeting